Sex difference in the expression of PD-1 of non-small cell lung cancer - Gu, Yong; Tang, Ying Y.; Wan, Jian X.; Zou, Jian Y.; Lu, Chuan G.; Zhu, Hao S.; Sheng, Si Y.; Wang, Yan F.; Liu, Hai Ch.; Yang, Jia; Hong, Hai (Frontiers in Immunology, 2022)
Background: Evidence increasingly indicated that lung cancer incidence in female continue to rise and women have a higher risk to develop adenocarcinoma than men. Male and female differ in their innate and adaptive immune responses, and there are sex differences in response to the PD-1/PD-L1-dependent blocking immunotherapy. Whether the differential expression of PD-1 between gender affect the response to blocking treatment, is currently unknown. Methods: We examined sex differences in serum sPD-1, mPD-1 expression on T cells and sex hormone levels in NSCLC patients. Statistical analysis was performed on the GraphPad Prism software version 5. The Mann–Whitney test (two-tailed) and non-paired Student’s t-test were performed to determine statistical differences in the two groups. Results: Our results revealed that higher level of sPD-1and expression of PD-1 on CD4+T cell in female patients than in male patients; we identified that serum sPD-1 level and the expression of mPD-1 on T cells was significantly reduced in NSCLC; we also found that serum testosterone level increased in female patient compare with control subjects, increased testosterone down-regulated the expression of mPD-1 on T cell. Conclusions: These finding provide a better understanding of the differences in PD-1 expression between genders in NSCLC patients and the effect of sex hormones on PD-1 expression, and supply evidence for early lung cancer diagnosis and responsiveness to immune checkpoint inhibitors.